Talking Story: Understanding Culture-based Curricula - Jamie Dela Cruz (International Journal of Pedagogy and Teacher Education, 2019)
The phenomenological study investigated the perceptions of teachers who implemented a culture-based curriculum at an elementary school on Oahu. Aloha ‘Āina is a culture-based curriculum with instruction and student learning grounded in the values, norms, knowledge, beliefs, practices, experiences, and language that are the foundation of the Hawaiian culture. Eight teachers were interviewed after they used the culture-based curriculum in their classrooms during one semester. Data analysis revealed four categories: teachers’ initial experiences, student engagement, challenges and opportunities, and meaningful experiences. Teachers were challenged by the culture-based education program and teachers’ perceptions of the Aloha ‘Āina curriculum were positive, most agreeing that it helped students to learn and improve student engagement through hands-on learning in and outside of the classroom.Keywords: Aloha ‘Aina, culture-based curricula, place-based education,